Early and long-term complications in haemodialysis vascular access - Szarnecka-Sojda, Anna; Miszczuk, Jarosław; Polewczyk, Anna (Medical Studies/Studia Medyczne, 2018)
The paper presents vascular accesses used for the purpose of haemodialysis in patients with end-stage renal disease. The recommendations of the NKF K/DOQI concern performing a first-time permanent access in the form of an autogenous fistula. Attention has been paid to accurate diagnostic imaging of blood vessels. Early and long-term complications of functioning fistulas are presented, together with the manner of their treatment. Dialysis catheters are also described as the only possibility of dialysis in patients with contraindications to the creation of fistulas. Bloodstream infections are the most common complication of dialysis with catheters. An important element of prevention is monitoring the function of catheters, which reduces the need for medical intervention. New solutions improving the functioning of vascular access have also been presented. Careful use of vascular access, as well as fistula and catheter site function monitoring, contributes to extending the lifespan of an access and reduces complications.